Funding Liquidity Risk, Bank-Specific Variables And Profitability Of Islamic Rural Banks - Jusuf, Nurain; Widarjono, Agus (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This research investigates the impact of funding liquidity risk and some bank-specific variables on the profitability of Islamic rural banks in Indonesia, for the case of Islamic rural banks located on Sumatera Island. This study examines 41 Islamic rural banks with quarterly data from 2019: Q1 to 2023: Q4. Panel regression with unbalanced panel data is then employed. For further analysis, we make an interaction between funding liquidity risk and bank size to investigate whether large banks benefit from their size associated with the impact of funding liquidity risk on profitability. Our results confirm that funding liquidity risk lowers profitability. More importantly, large Islamic rural banks face less risk associated with the impact of funding liquidity risk on profitability than small Islamic rural banks. Results also highlight the importance of strong bank fundamentals such as efficiency in supporting profitability. This research has two important implications, theoretically and practically. First, from a practical perspective, funding liquidity risk reduces profits because Islamic rural banks dare to take investment risks to obtain high income. Second, Islamic rural banks must be able to manage maturity mismatch so that the negative impact of funding liquidity risk on profits can be minimized.